2006
DOI: 10.1002/tox.20211
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity and bioaccumulation of aqueous and sediment-bound metals in the estuarine amphipodMelita plumulosa

Abstract: The sensitivities of juvenile and adult amphipods to metals (Cd, Cu, Ni, Pb, and Zn) in whole sediment and water-only exposures were compared using a newly developed acute test with the estuarine species Melita plumulosa. Endpoints included survival and bioaccumulation in adults, and survival and growth (body length) in juveniles over 96 h water-only and 10 day sediment exposures. Juveniles were more sensitive than adults to metals, either bound to sediments or in the aqueous phase. Although LOEC values for co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 29 publications
4
23
0
3
Order By: Relevance
“…Marine benthic diatom (Cylindrotheca closterium) showed high sensitivity, and the EC50 value was reported to be 26 mg/kg Cu spiked in natural marine sand [6], which is lower than the EC50 values from the present study for coarsegrained sediments (142 mg Cu/kg) and fine-grained sediment (1,189 mg Cu/kg). Previous studies also reported some lethal toxicity data such as median lethal concentration values of Cu-spiked sediments to Tubifex tubifex ranging from 88 to 106 mg/kg [30], median lethal concentration of 1,310 mg Cu/kg for adult and 790 mg Cu/kg for juvenile amphipod Melita plumulosa [31], and median lethal concentration values of 426 mg Cu/kg for Chironomus riparius larvae after 10 d of exposure to Cu-spiked sediments [32]. The present study and previous studies suggest that different species have variable sensitivity toward toxicants in sediments, and their toxicity can be influenced by toxicants and sediment components.…”
Section: Species Sensitivitymentioning
confidence: 94%
“…Marine benthic diatom (Cylindrotheca closterium) showed high sensitivity, and the EC50 value was reported to be 26 mg/kg Cu spiked in natural marine sand [6], which is lower than the EC50 values from the present study for coarsegrained sediments (142 mg Cu/kg) and fine-grained sediment (1,189 mg Cu/kg). Previous studies also reported some lethal toxicity data such as median lethal concentration values of Cu-spiked sediments to Tubifex tubifex ranging from 88 to 106 mg/kg [30], median lethal concentration of 1,310 mg Cu/kg for adult and 790 mg Cu/kg for juvenile amphipod Melita plumulosa [31], and median lethal concentration values of 426 mg Cu/kg for Chironomus riparius larvae after 10 d of exposure to Cu-spiked sediments [32]. The present study and previous studies suggest that different species have variable sensitivity toward toxicants in sediments, and their toxicity can be influenced by toxicants and sediment components.…”
Section: Species Sensitivitymentioning
confidence: 94%
“…1) is a commonly utilised sentinel species to assess the health of estuarine sediments (Ecotox Services Australasia, 2009). Originally isolated and described by Zeidler from specimens found in a coastal pool 100 m from the sea in northern New South Wales (Zeidler, 1989), M. plumulosa is an epibenthic amphipod endemic to eastern Australian waterways that can be found in the intertidal zone beneath rocks or shell-grit (King et al, 2006b;Lowry et al, 2000). Although the full geographic range of this amphipod has not been definitively established, historically it has been found in many waterways and estuaries between Brisbane and Melbourne along the east coast of Australia (Lowry et al, 2000); recently this amphipod has been sampled from the Pine River in Queensland down to the Yarra River in Victoria (Fig.…”
Section: Biology Of Melita Plumulosamentioning
confidence: 99%
“…plumulosa and can tolerate a wide range of environmental conditions, including sediment particle sizes ranging from silt to gravel, salinities ranging from freshwater to seawater, as well as a wide range of temperatures King et al, 2006b). Under laboratory conditions, the average lifespan of M. plumulosa is 8-11 months; gravid females release live young that become sexually mature in four to six weeks .…”
Section: Biology Of Melita Plumulosamentioning
confidence: 99%
See 2 more Smart Citations